Genetic diversity of sotol (Dasylirion cedrosanum Trel.) at different elevations - Rodríguez Herrera, Raúl; Reyes-Valdés, Manuel Humberto; Pinales-Quero, Irma; González-Vázquez, Víctor M.; Castillo, Francisco; Aguilar, Cristobal N. (Ecosistemas y Recursos Agropecuarios, 2017)
Genetic analysis is important to identify genetic variability in organisms inhabiting a speci c region. In this study, a sotol population was characterized through ve elevational levels at one location in the Chihuahuan Desert in Mexico, using ampli ed fragment length polymorphisms (AFLP) markers. Population genetic diversity, polymorphic loci, Nei’s unbiased heterozygosity, average and e ective number of alleles, and optimum number of samples were determined. A dendrogram was constructed, and Shannon entropy was calculated. Based on the estimated parameters, the middle elevational level had the highest genetic variation. The optimum sample size to determine genetic variability in sotol was from 24 to 26 plants. In the produced dendrogram, no association was observed among plants belonging to the same stratum, which could be explained by the high genetic ow among plants from di erent strata. These results provide a foundation of knowledge for understanding the genetic diversity in sotol populations growing in the Chihuahuan Desert mountains. The information will allow designing strategies for implementing sotol breeding and conservation programs.